Gardens in today’s schools. A sign of educational backwardness, or progress? - Kowalski , Ryszard; Grott, Edward (Studia Ecologiae et Bioethicae, 2015)
This article looks at school gardens and their importance in the environmental education of children and young people at all levels, including elementary, junior, and senior high schools. the authors raise the question as to whether, in today’s information-driven world, schools should continue to teach biology using natural samples such as the plants and animals available in the school garden, or whether they can be replaced by electronic means (e.g. a computer application), without negatively affecting educational quality. In answering this question, they come down resoundingly in favor of retaining the school garden as an essential and fundamental educational tool, which will never lose its relevance and use in the teaching of science. The authors suggest readdressing the existing definition of what a school garden is so that all teachers will come to understand that, regardless of whether the school is located in an urban environment or in the countryside, its natural environment can always be used in the teaching of biology and natural sciences and should, therefore, be defined as a school garden.